Compensation as Sanctions for the Perpetrators of Corruption in the Dimensions of Indonesian Criminal Law Renewal - Kurniawan, Kukuh Dwi; Indri Hapsari, Dwi Ratna; Fajrin, Yaris Adhial; Triwijaya, Ach. Faisol (Brawijaya Law Journal, 2019)
Corruption is one of the negative consequence of corporate crime. Corruption perpetrators from corporations are still relatively new in Indonesia, so legal reform is still needed, which is close to the purpose of criminal law. The existence of legal sanction in the form of compensation becomes a breakthrough for one type of sanction and can impose the perpetrator of corruption. Thus, in this study, we want to find a theoretical basis for corporate punishment that commits corruption and the existence of criminal sanctions for corporate compensation as perpetrators of corruption in efforts to renew criminal law. This study uses normative research by approaching the conceptual approach. From this research, finding a corporate foundation that commits corruption can be imposed by a criminal is in line with the purpose of punishment as well as by ius constituendum. For compensation that is an alternative to corporate punishment as a perpetrator of corruption, it can be brought down along with the principal penalty which has the purpose of accountability and reconciliation, guidance, reintegration, socialization or means of resolving conflicts to the community.